Coral Reefs Condition and Fish Abundance in Gilimanuk Waters, Jembrana Regency, Bali Province - Safli, Fuad Feisal; Yusrudin; Sumaryam (Indonesian Journal Publisher, 2025)
Coral reefs are complex marine ecosystems consisting of corals (Anthozoa), algae and other organisms (Barnes, 1987). They have an important role in maintaining the balance of marine ecosystems and provide habitat for many species of fish and invertebrates (Odum, 1993). The method used in the coral reef condition survey is the Underwater Photo Transect method. This method is a method for monitoring coral reef conditions. This method is a development of the Point Intercept Transect (PIT), Line Intersect Transect (LIT), and Rapid Reef Assessment (Towing) methods. According to the results of the study, location 2 has the highest percentage of live coral cover category of 16.77%, Furthermore, at location 1, the percentage of live coral was 13.21%, Based on the Decree of the Minister of Environment No. 4 In 2001, it was shown that the coral conditions at both points 1 and 2 were in the poor category. The abundance of coral fish in the Drinking Waters at station I point I has 5 species with an abundance of 46 individuals and an abundance of 0.46 (individuals/m3). Point II station I has 6 species of fish with 52 individuals and an abundance of coral fish 0.52 (individuals/m3).